Chemotherapy of Human African Trypanosomiasis - Bacchi, Cyrus J. (Interdisciplinary Perspectives on Infectious Diseases, 2009)
Human Africa trypanosomiasis is a centuries-old disease which has disrupted sub-Saharan Africa in both physical suffering and economic loss. This article presents an update of classic chemotherapeutic agents, in use for >50 years and the recent development of promising non-toxic combination chemotherapy suitable for use in rural clinics.